Nigeria what everyone needs to know - Campbell, John. (New York, NY Oxford University Press, 2018)
As the "Giant of Africa" Nigeria is home to about twenty percent of the population of Sub-Saharan Africa, serves as Africa's largest producer of oil and natural gas, comprises Africa's largest economy, and represents the cultural center of African literature, film, and music. Yet the country is plagued by problems that keep it from realizing its potential as a world power. Boko Haram, a radical Islamist insurrection centered in the northeast of the country, is an ongoing security challenge, as is the continuous unrest in the Niger Delta, the heartland of Nigeria's petroleum wealth. There is also persistent violence associated with land and water use, ethnicity, and religion.
Includes bibliographical references and index.
Keywords: Nigeria--History.